Evaluating medical students' ability to identify and report errors: finding gaps in patient safety education. Issue 1 (31st December 2022) - Lee, Sungjoon; Roh, HyeRin; Kim, Myounghun; Park, Ji Kyoung
ABSTRACT: Background: Although there are frequent complaints of medical students' incompetence in reporting errors, few studies have examined their error-reporting abilities in the real world. Objectives: Three sub-functions of self-regulation theory were used to evaluate medical students' ability to identify errors (self-monitoring), analyse root causes (self-judgment), and devise improvement plans (self-reactions). In addition, whether students reacted differently to their errors and those of others (three sub-functions) was also examined. Methods: A total of 952 patient safety reports were reviewed retrospectively, submitted by third-year medical students between 2016 and 2018. Data were quantitatively and qualitatively analysed to investigate who committed the error, to identify the type of error and its root causes, and to find suggested improvement plans. Chi-square and Fisher's exact tests were used to compare students' responses to error origins. Results: Students reported other errors more frequently than their own (67.6% vs. 32.4%). They reported common critical medical errors, including errors related to engaging with patients (34.5%), invasive procedures (20.2%), and infection (18.5%). The root causes identified were more precise than the improvement plans by the students (75.5% vs. 18.4%, respectively). The students' improvement plans were not practical, especially at the patient level (25.8%). When students committed errors, they considered human factors such as fatigue, scheduling, and training as the most common root cause, focussing on improvement plans at the individual level. Conclusions: The results suggest that students were good at self-judgment, but not at self-monitoring and self-reactions. They reacted differently, based on who committed the error. To enhance self-regulated learning, Educators should encourage students to confront their errors, reflect on their self-reactions towards errors, develop well-being with time management, and think about the meaning of patient-centredness. Finally, active participation in clinical clerkship longitudinally may provide students with opportunities to learn from their errors.